Boosting Corporate Performance: Green Accounting and Audit Quality Synergy - Tampubolon, Jhon Dogor; Siagian, Valentine; Rinendy, Jhon (Yayasan Ilomata, 2024)
This study aims to explore the impact of green accounting and audit quality on company performance in property and real estate companies listed in 2021–2022. This study used the purposive sampling method, observing 138 observations from 69 companies. This study uses 91 GRI G4 Framework criteria statements to assess the level of green accounting disclosure. Corporate performance in this study is measured by ROA, ROE, and NPM. The results of this study, based on statistical data, show that green accounting only has a significant positive effect on NPM. The results of the audit quality effect on ROA, ROE, and NPM indicate that the effect was positive and insignificant. Based on this study indicates that the effect of green accounting is only seen in NPM, for that in the future there should be more companies that voluntarily make corporate sustainability reports.